Plaza de Mercado Samper Mendoza: hito urbano (2020)
Thinking about human incentives, in all their activities and actions the physical space is involved. It is the stimulation of this space that can help to promote and magnify experiences; understanding the user as the engine of each architectural project for its development and effectiveness. For this reason, the search for everyday small elements, which are part of the daily life of specific groups of people (collectives), can be the way to approach the needs they have. In the case study of Los Mártires, aromatic plants become the main axis of the project to get closer to this intangible and cultural heritage; investigate the way in which pleasure is delighted for the sense of smell, who will give a party with the infinite aromas gratifying to the spirit. An aromatherapy that surrounds those who inhabit the market square and its surroundings; It is intended to enhance what is the Plaza de las Herbs through other stimuli, through other senses. It is then, when the reform of the Samper Mendoza market place becomes the project plan to promote market culture in the neighborhood, the town and, if possible, in the city.